Near Field Scanning Optical Microscopy (NSOM): Development and Biophysical Applications - Betzig, E. (1986)
A new method for high-resolution imaging, near-field scanning optical microscopy (NSOM), has been developed. The concepts governing this method are discussed, and the technical challenges encountered in constructing a working NSOM instrument are described. Two distinct methods are presented for the fabrication of well-characterized, highly reproducible, subwavelength apertures. A sample one-dimensional scan is provided and compared to the scanning electron micrograph of a test pattern. From this comparison, a resolution of > 1,500 Å (i.e., ≃λ/3.6) is determined, which represents a significant step towards our eventual goal of 500 Å resolution. Fluorescence has been observed through apertures smaller than 600 Å and signal-to-noise calculations show that fluorescent imaging should be feasible. The application of such imaging is then discussed in reference to specific biological problems. The NSOM method employs nonionizing visible radiation and can be used in air or aqueous environments for nondestructive visualization of functioning biological systems with a resolution comparable to that of scanning electron microscopy.